Population Genetic Structure of Meloidogyne javanica Recovered from Different Regions of Iran - Hesar, Abbas Mokaram; Rostami, Mahsa; Ghaderi, Reza; Danesh, Younes Rezaee; Jalal, Arshad [UNESP]; da Silva Oliveira, Carlos Eduardo [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2022)
In a survey of root-knot nematodes in Iran, twenty-nine populations were collected from eleven provinces. All populations were identified as Meloidogyne javanica based on morphological and morphometric characteristics of females, males, J2s, and perineal patterns. Sequence Characterized Amplified Region (SCAR) primers confirmed the morphological studies, and all these populations produced a specific band in 670 bp using Fjav and Rjav primers. Genetic structure analyses using the combination of RAPD and ISSR markers revealed four different groups, which was in agreement with UPGMA cluster analyses. These four groups were related to four different geographic regions with a high geographic distance. The total estimated genetic diversity was 8%, which was a low value. Values of FST and Nm were 0.628 and 0.148, indicating that populations of these four regions were separated from each other; however, some gene flow between them could be attributed to human activities. Mantel test also revealed a negative correlation between genetic diversity and geographic distance.
Keywords: genetic structure; nematode genetic diversity; nematode identification; nematode population; root-knot nematode